Primary and middle-school children’s drawings of the lockdown in Italy - Capurso, Michele; Buratta, Livia; Mazzeschi, Claudia (Frontiers in Psychology, 2022)
This retrospective-descriptive study investigated how primary and middle-school children perceived the first COVID-19 lockdown in Italy (March–May 2020) as manifested in their drawings. Once school restarted after the first COVID-19 wave, and as part of a structured school re-entry program run in their class in September 2020, 900 Italian children aged 7–13 were asked to draw a moment of their life during the lockdown. The drawings were coded and quantitatively and qualitatively analyzed; several pictorial examples are illustrated in this article. Most children used colorful and full-body representations of the self, but in almost half of the pictures drawn by older students, the self was either missing or represented without the face visible. Most children drew the interior of their houses, and the outside world was completely invisible in over half of the pictures. The most represented activities among younger students were playing or sport, followed by screentime or technology-use. Domestic routines and distance learning were also depicted. Most children, but predominantly girls, drew characters showing emotional cohesion clues, and more younger pupils and girls depicted contentment as their main emotion. Conflicting emotions were virtually non-existent. Our data suggest that children coped with the lockdown through play, screen, and technology use. The high incidence of the missing self-representation in preadolescents could indicate how the enforced loneliness and lack of direct physical contact with others impacted their perception of the self. The findings presented here deepen our knowledge of the dynamics connected to the effects of the COVID crisis on children and young people and show how drawings can provide a valuable window into children’s emotions and perceptions.